Perioperative the BTLA inhibitor (tifcemalimab) combined with toripalimab and chemotherapy for resectable locally advanced thoracic esophageal squamous cell carcinoma trial (BT-NICE trial): a prospective, single-arm, exploratory study - Ding, Chengzhi; Zhang, Yahao; Xia, Tian; Li, Jiwei; Yao, Wenjian; Zhang, Quan; Han, Zhijun; Wang, Jianjun; Cao, Zhikun; Hu, Jinlong; Wei, Li (Frontiers in Immunology, 2025)
BackgroundThe treatment of cancer has brought about a paradigm shift with the introduction of immune checkpoint blockade (ICB) therapy, which is mostly dependent on inhibiting PD-1/PD-L1 and CTLA-4. However, recent studies have shown limited efficacy of this treatment in esophageal squamous cell carcinoma (ESCC). Preliminary studies have found that tifcemalimab (the world’s first anti-BTLA blocking monoclonal antibody) combined with toripalimab (PD-1) and chemotherapy has shown favorable safety and efficacy in several solid cancers. This study aimed to evaluate the safety and efficacy of neoadjuvant tifcemalimab combined with toripalimab and chemotherapy following esophagectomy for resectable ESCC, and the association of adjuvant immunotherapy with improved survival outcomes.MethodsPatients with pathologically confirmed cT1b-3N1-3M0 or cT2-3N0M0 thoracic ESCC were treated with neoadjuvant tifcemalimab (200mg, iv, d1) in combination with toripalimab (240mg, iv, d1) and chemotherapy (paclitaxel 135-175 mg/m2, d1 + cisplatin 75 mg/m2, d1) every 3 weeks for 2 cycles. Patients undergoing esophagectomy with pathological complete response (pCR) were administered up to 15 cycles of adjuvant tifcemalimab (200 mg) and toripalimab (240 mg), whereas patients without pCR received tifcemalimab in combination with toripalimab and adjuvant chemotherapy for 2 cycles, followed by tifcemalimab in combination with toripalimab immunotherapy up to 13 cycles. The patient with incomplete resection was decided to receive radiotherapy after a multidisciplinary consultation. The primary endpoint of this study was the pCR rate. The secondary endpoints include major pathological response rate (MPR), objective response rate (ORR), disease control rate (DCR), adverse events, R0 resection rate, event-free survival (EFS), and overall survival (OS).DiscussionThe Ethics Committee of Henan Provincial People’s Hospital has approved the protocol (No 2024-132-03). This study is the world’s first prospective clinical trial to evaluate the safety and efficacy of the BTLA inhibitor in combination with PD-1 and chemotherapy as neoadjuvant/adjuvant therapy for locally advanced thoracic ESCC. We predicted that perioperative combination immunotherapy as a potentially preferred and effective treatment strategy may lead to better survival outcomes.